Knowledge, awareness, and practice on breast cancer among staff nurses in Sultan Ahmad Shah Medical Centre (SASMEC@IIUM), Kuantan, Pahang: preliminary findings - Sowtali, Siti Noorkhairina; Adzali, Fatin Noraliah; Nazli, Nor Syawanidamia (2020)
Introduction: Knowledge insufficiency and late detection may contribute towards the growing number of incidence and mortality rate of breast cancer in Malaysia. The aim of this study was to identify the socio-demographic and level of knowledge, awareness and practice on breast cancer among staff nurses of SASMEC@IIUM, Kuantan, Pahang. Materials and Methods: A cross-sectional study was conducted using self-developed questionnaires with good validity (CVI=88.3%) and reliability (Cronbach Alpha=0.87) among 50 nurses conveniently to assess their level of knowledge, awareness, and practice on breast cancer. Data was analyzed descriptively using SPSS version 23.0. Results: Among 50 nurses, 82% were female and Malays, 66% were married, while 16% had family history with breast cancer. Almost 56% had post-basic education and mean clinical experience of 6.6 (±6.28) years. The mean knowledge score on risk factors of breast cancer is 10.82 (±3.17), slightly lower than the 50th percentiles (11.00) and moderate knowledge score on sign and symptoms of breast cancer, [mean (SD)= 8.18 (±1.69)]. In terms of awareness and practice on breast self-examination, the score was moderate [mean (SD)= 74.04 (±25.07)] consequently [mean (SD)= 66.62 (±26.85)]. Conclusion and Recommendation: Overall, the knowledge of risk factors on breast cancer is still lower in comparison to knowledge of sign and symptoms. This consequently support the moderate score found on awareness and practice towards breast self-examination. Therefore, more awareness campaign and internal training should be conducted by the organization managerial to improve the healthcare professionals’ knowledge, awareness and practice on breast cancer as the front liners.